Study on the effect of some physical and chemical treatments on rooting behaviour of Soapnut (Sapindus mukorosii Gaertn.) cuttings under nursery condition - Mundhe, A.D.; Shamet, G.S.; Bandana, L.C. (Indian Journal of Agroforestry, 2020)
Cuttings of soapnut - Sapindus mukorossi were tested for their rooting response as affected by donor stage, pre-conditioning (girdling) and auxin treatments during monsoon (July-August) and spring (March-April) seasons. It was evident that girdled cuttings of seedling origin material exhibited significantly higher sprouting, rooting and root characteristics in the species. A maximum upto 90.00 per cent rooting was achieved when girdled cuttings from seedling donors were treated with 1.0% IBA+ 2% captan + 2% sucrose-talc during monsoon season. The treatment has potential to mass propagate species to produce uniform and quality planting stock for agroforestry and plantation forestry programme.